DISPOSABLE E-CIGARETTES AND ADOLESCENT NEUROLOGICAL DEVELOPMENT: A REVIEW OF POTENTIAL THREATS - Zuzanna Kaźmierczak,; Szymon Antoni Kaźmierczak,; Jakub Kowalski,; Natalia Sobieska, (International Journal of Innovative Technologies in Social Science, 2025)
The rapid proliferation of disposable e-cigarettes represents a new wave in the youth vaping epidemic, posing a significant threat to adolescent health. These devices are characterized by high-concentration nicotine salts, a vast array of youth-appealing flavors, and discrete, easy-to-use designs, which have led to alarming rates of initiation and use among teenagers. This review article aims to synthesize the current scientific literature on the neurological consequences of disposable e-cigarette use during the critical developmental window of adolescence. The methodology involved a structured review of literature from PubMed and other scientific databases from 2019 to the present. Key findings from the reviewed literature indicate that exposure to high levels of nicotine during adolescence can disrupt the maturation of the prefrontal cortex, leading to lasting deficits in cognitive functions, including attention, memory, and executive control. Furthermore, evidence points to a strong association between adolescent vaping and an increased risk for mood disorders, such as depression and anxiety, and a heightened vulnerability to addiction to other substances. The chemical constituents of e-liquids, including flavorings and heavy metals, may also contribute to neuro-inflammation and neurotoxicity. In conclusion, the use of disposable e-cigarettes by adolescents is a major public health crisis with potentially severe and long-lasting consequences for neurological development and mental health. Urgent regulatory action, targeted public health campaigns, and further longitudinal research are imperative to mitigate this threat.